Congenital Heart Diseases: The Broken Heart Clinical Features, Human Genetics and Molecular Pathways - Rickert-Sperling, Silke; Kelly, Robert G.; Driscoll, David J.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2016)
This book provides comprehensive insights into congenital heart disease from embryonic development through to clinical features, including human genetics and our current knowledge of the underlying molecular pathways. It is divided into three parts: an introduction to the development of the heart and its vessels, an overview of the molecular pathways affecting the development of various cardiovascular structures, and a main section focusing on the different types of structural and nonstructural congenital heart diseases, including their clinical features, underlying genetic alterations and related animal models and pathways. Taken together these chapters, which were written by and for clinicians and researchers, provide an integrated and cutting-edge resource for all those who want to learn more about both the clinical aspects and the genetic and molecular basis of congenital heart disease.
Section I: General introduction in cardiac development -- Section II: Different chapters covering the different types of congenital heart disease -- Section III: The overall perspective.
Keywords: Medicine; Human genetics; Molecular biology; Cardiology; Developmental biology; Biomedicine; Molecular Medicine; Cardiology; Developmental Biology; Human Genetics; Electronic books